Memories of Action: Tracing Film Society Cinephilia in India. (December 2018) - Ghosh, Abhija
The inception stories of early film societies in India from the 1940s to the 1960s reveal how these groups initiated an access to international, art and alternative cinemas through a network of circulation and exhibition created separately from mainstream cinema markets thereby forming a parallel network of societies, foreign consulates, embassies, government institutions and the National Film Archive of India (NFAI). This paper navigates the early history and memories of film societies in an attempt to map the cinephiliac energy of the film society movement through their erstwhile network of film travel. Using experiences, criticism and narratives of nostalgia published in film society journals, this paper reimagines the routes traversed by art cinemas and their cinephiles, enumerating specific activities around the film object. Observing urban film societies where film society cultures were initially conceptualized, thrived and whose histories are relatively renowned but also traces some significant small town societies which made the most of these circuits of film travel reaching out to non-metropolitan centers effectively transforming backyards into screening spaces and widening the scope of community participation around art cinemas.